(3GdHYK hGdfThQs - (3eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj, CHh YHO Gddg, GdbQWHj,J (B671 (3g` s ((3jhSa Hf YHO Gddg GdbTGei s)
(3ChdgG (B:s
(3CNHQfG eMeO Hf jMji Hf GdefPQ GdbQGA cGf Chd ef bGd HGdbOQ eYHO GdLgjfi HGdHUQI s
(3BNQgG (B:s
(3MJi jchfhG CeKGd GdOQ ecJhHI QbGHge GdLgfejhf YJbGA Gddg ajYQage Cgd GdLfI HPdc ai QbGHge Ke jbhdhf QHfG CeM YfG gPG GdcJGH ajeMGg Yfge Je cJGH GdHYK hGdfThQ s
(3HBNQgG SeGYGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B239s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B390s
Keywords: (3GdJhMjO hGdedd hGdfMds